The Effect of Using E-Book Learning Media on Folk Tales on the Reading Comprehension Ability of Fourth Grade Students - Selvina Damayanti; Ummu Khaltsum; Haslinda Haslinda (CV. Edujavare Publishing, 2026)
Education at the elementary school level plays a significant role in developing students’ literacy skills, particularly reading comprehension. This study aimed to determine the effect of folklore E-book learning media on the reading comprehension ability of fourth-grade students at UPTD SD Negeri 84 Barru. The study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. The participants consisted of 40 fourth-grade students divided into two groups: an experimental class and a control class, each consisting of 20 students. The experimental class received instruction using folklore E-book learning media, while the control class was taught using conventional learning methods. Data were collected through reading comprehension tests and classroom observations. The data were analyzed using descriptive and inferential statistical techniques, including normality tests, homogeneity tests, and an Independent Sample t-test. The results showed that the students’ reading comprehension ability improved significantly after the implementation of folklore E-book learning media. The mean score of the experimental class increased from 61.00 in the pretest to 82.25 in the posttest, while the control class improved from 56.50 to 76.50. Statistical analysis indicated a significant difference between the experimental and control groups, demonstrating that folklore E-book learning media had a positive effect on students’ reading comprehension ability. The findings suggest that folklore E-book media can create interactive, engaging, and meaningful learning experiences that support literacy development and increase students’ motivation in reading activities.